Humans and Uniqueness. (March 2015) - Schumpe, Birga Mareen; Erb, Hans-Peter
A defining force in the shaping of human identity is a person's need to feel special and different from others. Psychologists term this motivation Need for Uniqueness (NfU). There are manifold ways to establish feelings of uniqueness, e.g., by showing unusual consumption behaviour or by not conforming to majority views. The NfU can be seen as a stable personality trait, that is, individuals differ in their dispositional need to feel unique. The NfU is also influenced by situational factors and social environments. The cultural context is one important social setting shaping the NfU. This article aims to illuminate the NfU from a social psychological perspective.